2014
DOI: 10.5539/ijms.v6n1p45
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Market Environments on Marketing Relationships

Abstract: This paper addresses empirically two issues. One is whether or not basic marketing relationships at the establishment level are robust to a substantial change in the market environment. Another one is whether after this event takes place the marketing relationships for new establishments are the same as those for existing establishments. We rely on two data sets: a survey of gas stations in 1998 in Pamplona, Spain, when prices of gasoline products were fixed by the government; and a similar survey in 2007, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Setting out from a concept of distribution services similar to that analyzed in this paper, previous research has observed that the service assortment at the time of purchase, delivery assurance and the shopping ambience provided by retailers are the main contributors to customer satisfaction in the in-store shopping environment (Betancourt et al, 2007;Betancourt et al, 2014). The results of our analysis are consistent with these earlier findings.…”
Section: Discussionsupporting
confidence: 89%
“…Setting out from a concept of distribution services similar to that analyzed in this paper, previous research has observed that the service assortment at the time of purchase, delivery assurance and the shopping ambience provided by retailers are the main contributors to customer satisfaction in the in-store shopping environment (Betancourt et al, 2007;Betancourt et al, 2014). The results of our analysis are consistent with these earlier findings.…”
Section: Discussionsupporting
confidence: 89%
“…The fourth level is utilization of several econometric models [23][24]. These models include multiple linear In terms of forecasting, one of the major concern is prediction accuracy.…”
Section: Abroadmentioning
confidence: 99%